Family language policy in the Polish diaspora : a focus on Australia - Romanowski, Piotr, 1973- (New York : Routledge, 2021)
"This book explores language practices, beliefs, and management across a group of Polish immigrant families in Australia, drawing on these case studies as a lens through which to unpack dynamics of Family Language Policy (FLP) and their implications for future research on FLP. The volume begins by outlining the historical context of Polish immigration in Australia, charting two key waves of Polish migration in the 20th century and the subsequent unfolding of issues around language and culture maintenance in these families. This discussion paves the way for exploring key themes of language socialization, language ideologies, and heritage language maintenance and the affordances of FLP research in elucidating these dynamics at work in the lived experiences of a group of Polish immigrant families in Melbourne. The book highlights the importance of a triangulated approach, integrating qualitative and quantitative methods, in offering nuanced insights into parental approaches and children's experiences of a bilingual upbringing and the wider impact of FLP on transnational families. Opening up avenues for future research on Family Language Policy and better understanding the language practices of specific communities in a globalized world, this book will be of interest to scholars in multilingualism, sociolinguistics, and applied linguistics"--
Polish Immigration to Australia -- Intersections of Bilingual Development, Language Socialisation and Heritage Languages -- Family Language Policy -- Research Methodological Background -- Online Questionnaire -- Case Study Report One: Flexible Code-Switching Practices -- Case Study Report Two: A Restrictive One Parent -- One Language Strategy -- Case Study Report Three: Accommodating Dual-Lingual Interactions -- Discussion: Cross-Case Analysis -- Further Implications and the Way Forward.
OCLC-licensed vendor bibliographic record.
Keywords: Heritage language speakers -- Australia -- Melbourne (Vic.) -- Case studies; Bilingualism -- Australia -- Melbourne (Vic.) -- Case studies; Polish language -- Social aspects -- Australia -- Melbourne (Vic.); LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics